The management of psychosocial risks at work: state of the art and future perspectives - Iavicoli, Sergio; Di Tecco, Cristina (La Medicina del Lavoro, 2020)
Background: Psychosocial risk management represents a current challenge in Occupational Health and Safety (OSH) due to their impacts of such risks on work stress and the rapid changes of the world of work. An effective psychosocial risk management can be carried out on the basis of an integrated multidisciplinary model founded on the risk management paradigm. Over years, the occupational medicine has played an important role at national level in this area, contributing to the creation of an integrated and participatory approach. Objectives: This study explores the developmental process of psychosocial risk management over time in Europe and Italy, to offer an update on the state of the art at a national level and insights on future perspectives. Methods: Through a reflection on research developments, in Europe and in Italy, we outline how the knowledge obtained has been translated into policies, which have encouraged the implementation at international and national level of consolidated practices for the management of psychosocial risks. Results: An overview of some key steps of the inclusion of psychosocial aspects in OSH is presented, highlighting the positive impact of the multidisciplinary approach. Moreover, the driving role played by policies for implementation in organizational practice is also highlighted, with particular reference to the Italian example. Discussion: Starting from the existing knowledge, it is necessary to tackle emerging risks by continuing to translate the knowledge obtained from research into policies that have a driving role in the identification and implementation of actions and practical tools.